Front Cover: Controlling Activity of Heterogeneous Cu Single‐Atom Catalysts by Fine‐Tuning the Redox Properties of CeO2‐TiO2 Supports (ChemCatChem 8/2023). Issue 8 (4th April 2023) - Abdel‐Mageed, Ali M.; Cisneros, Sebastian; Mosrati, Jawaher; Atia, Hanan; Vuong, Thanh Huyen; Rockstroh, Nils; Wohlrab, Sebastian; Brückner, Angelika; Rabeah, Jabor
Abstract : The Front Cover presents a surface‐science approach to understanding and steering the catalytic properties of heterogeneous single‐atom catalysts (SACs) aiming to step them up for industrial applications. In their Research Article, A. M. Abdel‐Mageed et al. show that the CO oxidation activity of Cu/CeO2 ‐TiO2 SACs can be fine‐tuned by modulating the Ce/Ti ratio. The catalytic activity obeys a volcano‐shaped dependence of Ce/Ti molar ratio. Insights from operando spectroscopy and several other characterizations correlated the highest activity to the highest dispersion and reducibility of CeO2 nanoparticles which culminates around a Ce/Ti ratio of 0.18. Together with the atomically dispersed Cu species, the highly dispersed ceria nanoparticles constitute the catalytically active redox species (Cu 2+ −O−Ce 4+ − ⇆ −Cu 1+ −Ce 3+ −). This study highlights the synergism between the rational design of catalytic materials and the power of operando spectroscopy. More information can be found in the Research Article by A. M. Abdel‐Mageed et al.